2021
DOI: 10.1038/s41467-021-23230-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex as an important factor in nanomedicine

Abstract: Nanomedicine has demonstrated substantial potential to improve the quality and efficacy of healthcare systems. Although the promise of nanomedicine to transform conventional medicine is evident, significant numbers of therapeutic nanomedicine products have failed in clinical trials. Most studies in nanomedicine have overlooked several important factors, including the significance of sex differences at various physiological levels. This report attempts to highlight the importance of sex in nanomedicine at cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 131 publications
0
41
0
Order By: Relevance
“…Elevated level of monocytes is usually due to infections, blood disorders, or an increased immunogenic response. It is known that rodents have different innate/adaptive immune responses depending on their gender [ 35 ]. Female mice and rats demonstrate stronger phagocytic activity of macrophages than males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated level of monocytes is usually due to infections, blood disorders, or an increased immunogenic response. It is known that rodents have different innate/adaptive immune responses depending on their gender [ 35 ]. Female mice and rats demonstrate stronger phagocytic activity of macrophages than males.…”
Section: Discussionmentioning
confidence: 99%
“…Such a difference in the response of two animals’ sexes to external impact is quite understandable. Back in the 1990s the biomedical research community demonstrated the importance of sex as a biological variable in laboratory and clinical experiments [ 35 ]. This fact emphasizes the importance of this study carried out on both sexes of two animal species.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because recent reports revealed the critical role of sex in safety and therapeutic efficacy of nanoparticles. [ 206 ]…”
Section: In Vivo Antibacterial Impacts Of Npsmentioning
confidence: 99%
“…Due to the gene mutation of KRAS in many cancer patients, the clinical performance is not satisfactory ( Kim et al, 2020 ). Another specific example is that sex also plays a critical role in the drug response, toxicity and other aspects ( Hajipour et al, 2021 ). Therefore, precision medicine has received more and more attention in recent years, which could significantly compensate for the shortcomings of conventional strategies ( Figure 2 ).…”
Section: Nanomaterials Therapeutics Overcome Drug Resistancementioning
confidence: 99%